The tenuous perceptual border between real and virtual political action: a study in young Mexican university students - Pérez-Verduzco, Germán (2022)
This research aimed to study the perception of Mexican university students (n = 212) regarding a political action carried out in the physical and virtual space, also comparing various analytical dimensions: perceived cost, perceived benefit, perceived impact and perceived satisfaction. The study was quantitative, cross-sectional and correlational in design. In order to measure association between variables, we used Spearman's rho test, and to examine the underlying structure in the data, an exploratory factorial analysis and two confirmatory factorial analyses. The results show significant correlations between both modalities (virtual and physical), and that the difference between the four dimensions of action is greater than the difference between modalities. Such findings imply that, at least in perceptual terms, the difference between acting politically in cyberspace and doing so in the physical environment is very tenuous.